Effects of work climate, leadership, and motivation on individual performance in elective surgery delays - Ahmad, Ahmad; Sidin, Andi Indahwaty; Anggraeni, Rini; Pasinringi, Syahrir A.; Hamzah, Herlina A. (Edelweiss Applied Science and Technology, 2026)
Underutilized operating rooms caused by delays in elective surgery schedules contribute to extended waiting lists, patient dissatisfaction, and worsening clinical conditions, sometimes leading to preventable complications. These delays are often linked to organizational and human resource factors, highlighting the importance of work climate, leadership, and staff motivation in influencing individual performance. This quantitative cross-sectional study collected structured questionnaire data from 114 operating room personnel, including surgeons, anesthesiologists, nurses, radiographers, and pharmacy staff. Using SmartPLS path analysis, the study examined both direct and indirect relationships. Results indicated that work climate had a significant direct effect on individual performance (path coefficient = 0.30), while motivation showed a strong direct influence (path coefficient = 0.557). Leadership significantly impacted work climate (0.80) and motivation (0.70) but did not have a statistically significant direct effect on performance (0.016), suggesting its role is primarily mediated through other variables. Overall, work climate and motivation are key factors in managing elective surgery delays. Effective leadership plays an essential indirect role by fostering a supportive work environment and enhancing staff motivation. Hospital management strategies aiming to reduce surgical delays should focus on improving work climate and strengthening motivational systems, supported by adaptive leadership practices.